Redesain Sistem Penyediaan Air Minum (SPAM) Pedesaan di Desa Wiyono Kabupaten Pesawaran - Andre Velthuzend; Arif Dwi Prajasena; Suprapto Suprapto; Ismadi Raharjo (Jurnal Ilmiah Teknik Pertanian - TekTan, 2015)
In general, the construction of rural water supply system is made to the design and construction materials are inadequate, so as to have a short lifespan opration with a fairly high level of leakage as happened in the village Wiyono, Gedongtataan, Pesawaran District. The purpose of this study was to redesign the Water Supply SystemÂ  that already exist in the village Wiyono. The method used is the discharge measurements, measurements of topography, socio-economic surveys, calculation of water needs and budget plan (RAB), while the analysis of pressure and loss of water use Epanet program. Re-planning of water supply is done by counting the number of villagers until 2039 with the geometric method that is numbered 3,161 inhabitants. Discharge of water needed is 11,8 liters/sec, and a debit available on spring Wiyono of 55 liters/sec it is still insufficient to discharge water needs until the year 2039. The results of the measurement of topographic maps obtained height difference between springs with the service area is 113 m above sea level, then the drinking water distribution system uses gravity drainage system. EPANET hydraulic analysis results using the highest pressure is 47,05 and the lowest pressure that is 0,04 so that type of pipe used is PVC pipe with a diameter of between 26-140 mm in length of 5,090 meters. To reduce water turbidity due to changes in the level of turbidity then made slow sand filter basin with a length of 9.5 meters, a width of 4 meters and a height of 2,7 meters. Based on the results of the calculation of the Draft Budget (RAB) The investment needed is Rp. 1,060,000,000.00 with a 25-year life of the project, the obtained prices per m3 of clean water in Hamlet IV Sumberejo Rp. 700,00/m3. Keywords: rural water supply system, gravity system, hydraulic analysis, the price of water